Family Efforts to Prevent Transmission of Tuberculosis Disease in The Region of Kawangu Community Health Center East Sumba Regency - Gunawan, Yosephina Elizabeth Sumartini (Jurnal Keperawatan Soedirman, 2019)
Introduction: The family has an important role in the care and treatment of tuberculosis as well as the prevention of transmission of tuberculosis disease in the family or the community. This research aims to identify the family's efforts in preventing the transmission of tuberculosis disease in the region of Kawangu Community Health Center East Sumba Regency. Method: This study is a qualitative research approach phenomenology with the participant as much as 16 people selected by purposive technique. Data collected by conducting structured interviews and dianalis with the technique of content analysis. Result: The theme of the research obtained is as much as 7 themes in a row as follows: the concept of Disease tuberculosis, Cleanliness, Close your mouth when coughing or sneezing, dispose of the saliva in place, Support TB Disease Treatment, improved nutritional Status and puts Sufferers Separately. Conclusion: Although the family has yet to fully grasp the concept of disease of TB but various efforts have been undertaken by the family to prevent the transmission of tuberculosis diseases such as keep clean, reminds patients to cover the mouth when coughing/sneezing and not throw the saliva carelessly. The family also support treatment programs with a role as PMO as well as pay attention to nutrient intake for patients of TB. Other efforts undertaken family is placing the sufferer separately.Keywords: family efforts, prevent transmission, tuberculosis